The Influence of Different Grafting Materials on Alveolar Ridge Preservation: a Systematic Review - Jad Majzoub; Andrea Ravida; Thomas Starch-Jensen; Mustafa Tattan; Fernando Suárez-López del Amo (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of the present review was to evaluate the effect of different bone substitutes used for alveolar ridge preservation on the post extraction dimensional changes.